CRIMINAL PROVISIONS FOR PERPETRATORS OF TERRORISM FROM THE PERSPECTIVE OF INDONESIAN CRIMINAL LAW - Jacky Wicaksana; Fitria Ramadhani Siregar; Abdul Razak Nasution (CV. RADJA PUBLIKA, 2025)
Terrorism is an extraordinary crime that requires extraordinary measures. Terrorism has become a global phenomenon that has spread to almost every country in the world, including Indonesia. As in other regions, terrorism in Indonesia also has a theological and ideological basis and networks that make it strong resistance. To date, the crime of terrorism is one of the serious threats to national security. Terrorism is a theme that attracts the attention of many groups, especially academics, to study it from various aspects. Acts of terrorism often occur in Indonesia. The incident that occurred domestically, which made the image of Indonesia as a country that is unsafe for foreign citizens was the case of the Bali Bombing. Indonesian society generally condemned the act. The crime of terrorism resulted in the death of many victims, is very contrary to the Qur'an and Law Number 5 of 2018, so that the perpetrators must be subject to criminal sanctions or punishment as a result of their actions, namely the death penalty. This study uses a normative juridical approach method, with analytical descriptive research specifications. The data used in this study are secondary data obtained through literature studies, then analyzed qualitatively using law enforcement theory and Islamic justice theory. The results of this study are that the Government has made a new law in an effort to prevent acts of terrorism, namely Law Number 5 of 2018 concerning Amendments to Law Number 15 of 2003 concerning the Determination of Government Regulations in Lieu of Law Number 1 of 2002 concerning the Eradication of Criminal Acts of Terrorism into Law. Article 6 explains that: